Trust and responsibility in molecular tumour boards - Merry, David; Schickhardt, Christoph; Mehlis, Katja; Winkler, Eva C. (Bioethics, 2018)
Molecular tumour boards (MTBs) offer recommendations for potentially effective, but potentially burdensome, molecularly targeted treatments to a patient's treating physician. In this paper, we discuss the question of who is responsible for ensuring that there is an adequate evidence base for any treatments recommended to a patient. We argue that, given that treating oncologists cannot usually offer a robust evaluation of the evidence underlying an MTB's recommendation, members of the MTB are responsible for ensuring that the evidence level is adequate. We explore two models for how to share responsibility between MTB members. According to the first model, each MTB member, as well as the treating physician, should be held maximally and equally responsible for the recommendations. We argue that this insufficiently accounts for differences in roles and expertise of MTB members. We propose instead that responsibility is delegated via relationships of trust. We argue if these relationships of trust are to be instances of reasonable trust, (a) MTBs should offer a clinical representative to whom a treating physician may delegate the responsibility of ensuring there is sufficient evidence for treatment recommendations, (b) the relationships of trust between the representative and the other MTB members should be clearly defined, and (c) MTB members should be carefully selected. Treating oncologists retain a responsibility to consider general limitations of the evidence for targeted treatments in assessing whether the treatment recommendation offered by an MTB's representative is adequate for a given clinical situation.
Gesehen am 07.04.2020